2012
DOI: 10.4172/2165-8056.1000102
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Haemorrhagic Enteritis in Dairy Goats and the Effectiveness of Probiotic and Prebiotic Applications in Alleviating Morbidity and Production Losses

Abstract: The present study aims to investigate whether the disease complex for Haemorrhagic Enteritis (HE) in goats during the winter months is the same as described for Jejunal Haemorrhage Syndrome (JHS) in cattle. The further goal is to determine whether prebiotic and probiotic management strategies developed for JHS in cattle alleviate HE in goats. The clinical, necropsy and microbiologic findings were evaluated for goat cases during a natural HE outbreak. Bacterial pathogens were identified using selective media, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…O6, O26 and O157 were detected to be haemolytic but O8, O101 and O153 were non-haemolytic on 10% sheep blood agar as per this study. These findings are also matching with the earlier reports by Beutin et al (1993), Rodrigues et al (2004), Manna et al (2005) and Baines et al (2011).…”
Section: Resultssupporting
confidence: 93%
“…O6, O26 and O157 were detected to be haemolytic but O8, O101 and O153 were non-haemolytic on 10% sheep blood agar as per this study. These findings are also matching with the earlier reports by Beutin et al (1993), Rodrigues et al (2004), Manna et al (2005) and Baines et al (2011).…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, the ExPEC was almost absent from the tissue or digesta of the calves that succumbed to disease without warning in production site A. We previously reported STEC co-infections involved with HE in goats [20] and JHS in older calves and mature cattle [1,2]. The current study extends this list to include HE in calves less than one month old.…”
Section: Resultsmentioning
confidence: 67%
“…We hypothesized that if STEC mixtures did promote infection, natural disease outbreaks should have STEC co-infections. We initially examined natural JHS or HE cases in immature and mature ruminants [1,2,20] and a minimum of two genetically distinct STECs were involved in the co-infections. In the current study, we further extend the significance of STEC co-infections to include HE cases in immature calves.…”
Section: Discussionmentioning
confidence: 99%
“…They are also associated with a greater impact on microbial populations and nutrient digestibility, as well as volatile fatty acid content [50]. Mycotoxins and Shiga toxin-producing Escherichia coli infections are part of the disease complex for Haemorrhagic Enteritis during the winter months when animals consume moldy feed, and studies have shown that they can be controlled by the use of prebiotics and probiotics [51].…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%